Metabolomics profile responses to changing environments in a common bean (Phaseolus vulgaris L.) germplasm collection. (15th February 2022) - Mecha, Elsa; Erny, Guillaume L.; Guerreiro, Ana C.L.; Feliciano, Rodrigo P.; Barbosa, Inês; Bento da Silva, Andreia; Leitão, Susana T.; Veloso, Maria Manuela; Rubiales, Diego; Rodriguez-Mateos, Ana; Figueira, Maria Eduardo; Vaz Patto, Maria Carlota; et al.
Highlights: There was a clear genotype × environment interaction on beans metabolomics profiles. Heat stress increased salicylic acid and decreased some saponins' contents. A complexity of interactions supported common precursors in the metabolic routes. White accessions presented the highest percent area of organic oxygen compounds. Colored accessions presented the highest percent area of phenylpropanoids. Abstract: Metabolomics is one of the most powerful - omics to assist plant breeding. Despite the recognized genetic diversity in Portuguese common bean germplasm, details on its metabolomics profiles are still missing. Aiming to promote their use and to understand the environment's effect in bean metabolomics profiles, 107 Portuguese common bean accessions, cropped under contrasting environments, were analyzed using spectrophotometric, untargeted and targeted mass spectrometry approaches. Although genotype was the most relevant factor on bean metabolomics profile, a clear genotype × environment interaction was also detected. Multivariate analysis highlighted, on the heat-stress environment, the existence of higher levels of salicylic acid, and lower levels of triterpene saponins. Three clusters were defined within each environment. White accessions presented the lowest content and the colored ones the highest levels of prenol lipids and flavonoids. Sources of interesting metabolomics profiles are now identified for bean breeding, focusing either on local or on broad adaptation.